Fall Prevention in Older Adults: Insights from Saudi Arabian Physical Therapists on the Otago Exercise Program - Alsaleh,Hussam; Alsaad,Saad; Alabdulwahab,Sami; Vennu,Vishal; Bindawas,Saad (Risk Management and Healthcare Policy, 2024)
Hussam M Alsaleh,1,2 Saad M Alsaad,3 Sami S Alabdulwahab,1 Vishal Vennu,1 Saad M Bindawas1,4 1Department of Rehabilitation Sciences, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 2Department of Physical Therapy, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 3Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4King Salman Center for Disability Research, Riyadh, Saudi ArabiaCorrespondence: Saad M Bindawas, Department of Rehabilitation Sciences, College of Applied Medical Sciences, King Saud University, 10219, Riyadh, 11433, Saudi Arabia, Tel +966114696226, Email sbindawas@ksu.edu.saPurpose: Falls among older adults are a growing public health concern in Saudi Arabia. The Otago Exercise Program (OEP) is an evidence-based intervention aimed at reducing fall risk in this population. This study assessed the knowledge and attitudes of Saudi Arabian physical therapists toward the OEP and examined potential gender-based differences.Patients and Methods: A cross-sectional survey was conducted between November 2023 and April 2024, involving 120 licensed physical therapists from Saudi Arabia, recruited via Email and social media. The survey captured sociodemographic data, knowledge, and attitudes regarding the OEP. Responses were analyzed using descriptive statistics, chi-square tests, and Cramér’s V to assess the strength of associations, with a significance level set at p < 0.05.Results: Most physical therapists reported knowledge of the OEP’s clinical effectiveness (36.7%), cultural compatibility (35.0%), and fall prevention benefits (28.3%). Gender was not significantly associated with knowledge of clinical effectiveness (χ² = 3.84, p = 0.57), contraindications (χ² = 4.44, p = 0.48), cost-effectiveness (χ² = 4.15, p = 0.52), or fall prevention in older adults (χ² = 2.44, p = 0.78), with moderate effect sizes observed (Cramer’s V = 0.233 to 0.467). Attitudes toward the OEP were generally ...